Pass-through of Competitors' Exchange Rates to U.S. Import and Producer Prices - Pennings, Steven (World Bank, Washington, DC, 2017)
This paper shows that in theory and BLS microdata, the prices of imported goods respond to the exchange rates (ER) of the producer's foreign competitors. In contrast, standard models have no role for competitors' ERs. Excluding the effects of competitors' exchange rates typically biases upwards estimates of bilateral exchange rate pass-through because competitors' ERs and bilateral ERs are positively correlated. A multi-country version of Atkeson and Burstein's (2008) industry aggregation model is able to explain a sizable proportion of pass-through of competitors' exchange rates to import prices, and also predicts pass-through of foreign competitors' prices and pass-through of competitors' ERs to US producer prices -- both of which are supported in the data. The results suggest that pass-through will be larger for ER movements shared by a greater fraction of foreign competitor countries.